Antineoplastic effect of the flavonoid quercetin in a kaposi͛´s sarcoma cellular model - Lezcano, Virginia Alicia (2020)
Quercetin (QUE) is a flavonoid present in a wide variety of foods with different biological andpharmacological effects such as antitumor activity. Kaposi͛s sarcoma (KS) is a malignant Herpesvirusinduced tumor characterized by angiogenesis and proliferation of cells with characteristics of activatedendothelial cells. In this work we studied the antineoplastic effect of QUE and the modulation ofERK1/2, AKT and Wnt/ɴ-catenin signaling in a KS cellular model. Tumor cells were treated with QUE atdifferent concentrations (1-50 μM) for 24 and 48 h. Crystal violet staining revealed that QUEsignificantly decreases cell proliferation in a dose and time dependent manner: 77.8±5.1% 20 μM vs. Cand 85.7±7.5% 50 μM vs. C (24 h); 66.4±6.3% 10 μM vs. C, 55.9±2% 20 μM vs. C and 50.8±7.3 50 μMvs. C (48 h). In concordance, representative images showed an increase of cells with apoptoticcharacteristics. MTS assay demonstrated a significant decrease in cell viability at highest doses of QUE(84.4±7.1% 20 μM vs. C; 86±6.9% 50 μM vs. C) at 24 h and (63.7±7% 10 μM vs. C; 43.3±5.7% 20 μM vs.C; 34.3±7% vs. C) 48 h. Under the same experimental conditions, phosphorylated ERK1/2 and AKTwere analyzed by Western blot (WB) revealing an increment in their phosphorylation levels in a dosedependent way after 24 h of QUE. Since Wnt/ɴ-catenin signaling pathway play an important role intumor development and is activated in KS, ɴ-catenin protein levels were also analyzed by WB showingan increment of its expression from 5 μM of QUE. Altogether, these results demonstrate an antitumoreffect of QUE on KS cellular model, accompanied by ERK1/2 and AKT activation and an increase in ɴcatenin expression, a key protein of Wnt signaling pathway.